Chitosan (CTS) induced secondary metabolite production in Canscora decussata Schult. - An endangered medicinal plant (Kuwait Journal of Science)
Bioengineering has excellent potential in plant-based in vitro cultures for efficiently synthesizing desired plant products. Due to the rapid destruction of natural habitats, in vitro methods might save endangered species. Winged-Stem Canscora is an endangered medicinal herb used in traditional medicine for brain disorders. This study investigates the induction of in-vitro metabolite production using chitosan. Among the various concentrations of auxins tested, 82% of callus was obtained from Murashige and Skoog (MS) medium with 3 mg L−1 Kinetin (KIN) + 1 mg L−1 1-Naphthaleneacetic acid (NAA). The highest callus content was after the 3rd subculture at 200 mg L−1 chitosan treatment. On the 70th day of culture, levels of total phenolics and flavonoids are increased in the elicited and normal callus. However, antioxidant activity was higher in elicited callus compared to normal callus and wild plants. Higher secondary metabolite concentrations of elicited callus have superior anti-bacterial and anti-fungal activity. Secondary metabolites from elicited callus have a lower inhibitory concentration than those from wild plant and normal callus. High-performance thin layer chromatography (HPTLC) analysis showed that the elicited callus had higher amounts of mangiferin (0.178 μg mL−1) and scopoletin (0.133 μg mL−1). An efficient approach was employed to ensure that sufficient amounts of the widely used plant secondary metabolites from medicinal plants, such as mangiferin and scopoletin, were accessible to meet demand. © 2024